Abortion Once Again: a response to Feser, Goodwin, Mosquito, Sadowsky, Vance and Watkins - Block, Walter (Revista de Investigações Constitucionais, 2017)
Only a libertarian would think to base an analysis of the abortion controversy on private property rights. The present paper does just that. On that basis, it concludes that evictionism is the only policy compatible with libertarianism. This essay then uses this analysis to criticize the views on this subject of five scholars associated with this political philosophy: Feser, Goodwin, Mosquito, Sadowsky, Vance and Watkins.